SOCIAL PROBLEMS IN EKA KURNIAWAN’S NOVEL CANTIK ITU LUKA - Nurul Azmi; M. Manugeren; Purwarno Purwarno (JOURNAL OF LANGUAGE, 2023)
The research is related to social problems. People's lives are actually changing with the times. In the process of the changing, sometimes unexpected conditions arise or should not occur. This unexpected condition gradually becomes a polemic and has a negative impact on people's lives. This condition is called a social problem. Social problems cannot be ignored because they can disrupt global economic and political stability. The discussion of this research focuses on two social problems: poverty and prostitution. Poverty is the condition of a person who has no wealth, lacks, or has very low income and of course cannot fulfill his daily needs; while poverty is also closely related to prostitution. One can become a prostitute because of poverty or circumstances. Prostitution is a sexual activity outside the institution of marriage and is generally carried out by women. These two social problems can be found not only in the novel but also in the real world; so the sociology of literature is used as an approach in this research. The whole research is conducted using a qualitative descriptive method because the focus of the research is related to social problems. The results of the analysis show that this novel provides two descriptions of social problems: poverty and prostitution and these two social problems are clearly illustrated through the data obtained from the novel.